Odpowiedzi

Najlepsza Odpowiedź!
2009-10-07T20:21:11+02:00
3(x-y)=3x-3y
4(a+b)=4a+4b
-2(2x-y)=-4c+2y
-5(-3a+2+b)=15a-10-5b
4(-2x+y-1)=-8x+4y-4
-3(2-2xy+5y)=-6+6xy-15y

x²/2-x/2=x²-x=x(x-1)
3a²/5+6a/5=3a²+6a=3a(a+2)
¾p²q-¾pq²=¾pq(p-q)

-5(x-y-z)=-5x+5y+5z
2(3x-2y+3z)=6x-4y+6z
4x(x²-6xy)=4x³-24xy
-3xy(x+y-3)=-3x²y-3xy²+9xy
-2√2x(x+√2)=-2√2x²-4x=-2x(√2x+2)

6x-4y+6z=3(3x-2y+3z)
9xy-3x²y-3xy²=3xy(3-x-y)
-2√2x²-4x=-2x(√2x+2)
-5x+5y+5z=5(-x+y+z)
4x³-24x²y=4x²(x-6y)
2009-10-07T23:09:44+02:00
3(x-y)=3x-3y
4(a+b)=4a+4b
-2(2x-y)=-4x+2y
-5(-3a+2+b)=15a-10-5b
4(-2x+y-1)=-8x+4y-4
-3(2-2xy+5y)=-6+6xy-15y

x²/2-x/2=x²-x=x(x-1)
3a²/5+6a/5=3a²+6a=3a(a+2)
¾p²q-¾pq²=¾pq(p-q)

-5(x-y-z)=-5x+5y+5z
2(3x-2y+3z)=6x-4y+6z
4x(x²-6xy)=4x³-24xy
-3xy(x+y-3)=-3x²y-3xy²+9xy
-2√2x(x+√2)=-2√2x²-4x=-2x(√2x+2)

6x-4y+6z=3(3x-2y+3z)
9xy-3x²y-3xy²=3xy(3-x-y)
-2√2x²-4x=-2x(√2x+2)
-5x+5y+5z=5(-x+y+z)
4x³-24x²y=4x²(x-6y)